Influence of clinical pharmacist counseling on tamoxifen-related knowledge and adherence among women with breast cancer - Hala Saad Bash; Ihsan Salah Rabea (Pharmacia)
Seventy women with breast cancer who visited the center monthly to receive tamoxifen were randomized into two groups: a control group, which received the standard course of treatment, and an intervention group, which received the standard course of treatment in addition to pharmacy consultations. A statistically significant difference in knowledge scores was observed between the control and intervention groups at three months post-intervention (P < 0.001). Furthermore, a significant improvement in knowledge scores was noted within the intervention group when comparing baseline and three months post-intervention scores (P < 0.001). A significant improvement in adherence scores was also observed within the intervention group between baseline and three months post-intervention (P < 0.001). Additionally, a statistically significant difference in adherence scores was found between the control and intervention groups at three months post-intervention (P < 0.001). Our findings demonstrated a noticeable improvement in the knowledge and adherence levels of participants as a result of pharmacy consultation.